Relationship between destination brand image and destination brand loyalty of Gilgitbaltistan, Pakistan: a moderated mediation model - Hussain, Ibrahim (2022)
The main purpose of this research is to examine the causal association between the brand image and brand loyalty of Gilgit-Baltistan (GB), Pakistan as an international travel destination. This study suggests that destination brand image and destination brand loyalty are multidimensional constructs, each having two dimensions. The dimensions of the destination brand image are Destination Brand Association (DBA) and Destination Brand Personality (DBP). Meanwhile, the two dimensions of destination brand loyalty are Destination Behavioral Loyalty (DBL) and Destination Attitudinal Loyalty (DAL). A quantitative method with a deductive approach was used. The data was collected using an e-mail survey targeting international tourists who have been to GB, Pakistan at least once. The survey instrument was developed using Google form. Around 300 questionnaires were delivered to international tourists, 159 of which were retained and valid for evaluation. A series of exploratory and confirmatory factor analyses were employed to evaluate the dimensions, validity and composite reliability of the research constructs. Structural Equation Modelling (SEM) was used to evaluate the hypotheses of the research model. Six of the eight hypotheses were confirmed. When the antecedents were added, the research model showed that DBA and DBP are important determinants of DAL, with DAL being a strong antecedent of DBL. The relationships between the two dimensions of destination brand image and DBL were also significantly mediated by DAL. Destination perceived value (DPV), destination perceived quality (DPQ), and destination perceived safety and security (DPSS) were also examined as moderating variables on path ‘b’ of the model. The results show that DPV had a significant moderating effect on the indirect causal association between DBA and DBL, while the other two moderators had no significant effects. The results of this research suggest that the proposed dimensions of destination brand loyalty and destination brand image do support the research model. The study results may help destination marketing managers examine the destination brand image and destination brand loyalty more accurately, and develop and apply viable, competitive, and effective strategies for international mountainous travel destinations.